Achieving Gender Equality and Women’s Empowerment in Smallholder Adaptation: Lessons from IFAD’s Adaptation in Smallholder Agriculture Programme - Sriram, Vidhya (2018)
Key messages In order to achieve outcomes for gender equality and women’s empowerment in smallholder adaptation projects, project designers and implementers should:  Consider differential needs and priorities of women, so that project activities are designed to address the context in which women live and to support the activities they engage in.  Consider differential vulnerability of women to climate change.  Understand that participation does not necessarily translate into impact. Interventions need to consider norms, roles and relations and how these can evolve to promote gender equality and women’s empowerment in programs; and consult with women in the development and implementation of project activities.  Invest in staff capacity to implement gender action plans and mainstream gender in program activities.  Build the capacity of local institutions to support commitments to gender equality and women’s empowerment. This brief summarizes findings from the “Adaptation in Smallholder Agriculture Programme (ASAP) gender assessment and learning review” undertaken by consultants Catherine Hill and Greg Scarborough and technical staff from CARE. This gender assessment and learning review focused on eight projects co-funded by ASAP in Bangladesh, Cambodia, Ghana, Mali, Mozambique, Rwanda, Uganda, and Vietnam. The assessment and learning review provides lessons learned after three years of ASAP operation. The purpose of this study was to understand how the translation from design to implementation is happening in practice, and to generate insights and lessons from some of the ASAP-supported projects on the different barriers, opportunities, and experiences regarding gendermainstreaming and women’s empowerment.